2013
DOI: 10.1093/rheumatology/ket132
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum levels of 25-hydroxyvitamin D and osteoarthritis: a systematic review

Abstract: 25-(OH)D appears to be implicated in structural changes of knee OA rather than symptoms, and further well-designed RCTs are required to determine whether vitamin D supplementation can slow disease progression. There is insufficient evidence for other sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
72
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 51 publications
1
72
1
2
Order By: Relevance
“…6,8,13,16 Low serum 25-OH vitamin D increases osteoblastic activity and bone turnover. 1,9,14,17 Many mechanisms were put forwarded to explain role of vitamin D and alterations in properties of bones in the progression of the disease osteoarthritis. Increasing bone resorption by the elevated levels of parathyroid hormone (PTH) increasing bone turn over, or effect of vitamin D metabolites directly on articular chondrocytes were some of the mechanisms put forwarded to explain the role of vitamin D deficiency in osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,8,13,16 Low serum 25-OH vitamin D increases osteoblastic activity and bone turnover. 1,9,14,17 Many mechanisms were put forwarded to explain role of vitamin D and alterations in properties of bones in the progression of the disease osteoarthritis. Increasing bone resorption by the elevated levels of parathyroid hormone (PTH) increasing bone turn over, or effect of vitamin D metabolites directly on articular chondrocytes were some of the mechanisms put forwarded to explain the role of vitamin D deficiency in osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…12,16 In a recent study, decreased serum level of 25-hydroxy vitamin D was reported in a significant proportion of patients with OA of hip and knee joints. 14,[16][17][18][19] All these epidemiological suggests that by achieving normal serum vitamin D level may prevent or delay loss of cartilage loss and reduce the pain and other symptoms of OA. [15][16][17][18] Observation from studies on knee osteoarthritis evaluated by Cao et al suggested that serum 25-OH vitamin D level play an important role in structural changes of knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on prior recommendations (Cao et al, 2013), we used the following grading system. Strong evidence: 2 high-quality studies in agreement about an outcome; moderate: 1 high-quality + 1 medium quality, or 3 medium-quality studies in agreement; low: 1 high quality, or 2 medium-quality, or 3 low studies in agreement; no evidence: 1 medium-quality study, or < 3 studies of low quality studies, or any number of no quality studies in agreement, or no studies at all; conflicting: contrasting findings of low to strong evidence among studies.…”
Section: Discussionmentioning
confidence: 99%